Electroacoustic analogies applied to acoustic oscillator analysis - BUDZYŃSKI, G.; SANKIEWICZ, M. (Archives of Acoustics, 1994)
Analogies were, so far, rarely applied to acoustic oscillator analysis, however, their use turns out to be advantageous. It allows, due to comparison of analogous electric and acoustic oscillators operation, for better understanding of the process of oscillation maintenance, as well as, the interpretation of the circuits behaviour. Particular conclusions are presented relative to examples of a bowed string, and of a labial pipe oscillators.